2014
DOI: 10.4028/www.scientific.net/amm.487.488
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Self-Loosening of Bolted Joints under Cyclic Transverse Loads

Abstract: Self-loosening is one of the major failure reasons for bolted joints. Utilizing the finite element method, a 3-Dimension finite element model under dynamic shear loading is built to study the loosening of bolted fastener phenomenon. And the effect of increment step length, initial clamping force, amplitude of the shear load, thread tolerance, friction coefficients on the loosening process are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It was found that loosening was more difficult to occur under a fine thread, small excitation amplitude and initial preload, and large thread and bearing friction coefficients. Hou and Liao [115] investigated the effect of increment step size, initial clamping force, amplitude of the shear load, thread tolerance, and friction coefficients on the loosening process. An important finding was related to the friction coefficients, which indicated that the bolted joint would not loosen when the two coefficients |www.Springer.com/journal/40544 | Friction http://friction.tsinghuajournals.com were significantly different from each other.…”
Section: Feamentioning
confidence: 99%
“…It was found that loosening was more difficult to occur under a fine thread, small excitation amplitude and initial preload, and large thread and bearing friction coefficients. Hou and Liao [115] investigated the effect of increment step size, initial clamping force, amplitude of the shear load, thread tolerance, and friction coefficients on the loosening process. An important finding was related to the friction coefficients, which indicated that the bolted joint would not loosen when the two coefficients |www.Springer.com/journal/40544 | Friction http://friction.tsinghuajournals.com were significantly different from each other.…”
Section: Feamentioning
confidence: 99%
“…The loosening of bolted joint structures is affected by a variety of uncertainties, such as structural dimensions, external loads, and service environment. In recent years, scholars at home and abroad have studied the loosening behaviour, loosening mechanism, and anti-loosening methods of bolted structures by various means such as loosening test and finite element simulation [4][5][6][7], and some key results have been obtained. Still, no report has been reported on the systematic summarization of these research results.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-static simulation of vibration frequency was usually applied in the FEA, 911 which assumed that the magnitude of vibration frequency would not affect the loosening behavior. However, there were also researches 15 showing that vibration frequency had an important effect on the loosening behavior. This result contradicted the quasi-static assumption.…”
Section: Introductionmentioning
confidence: 99%